Developing as Animation Video for Teaching and Learning Writing Descriptive Text for Seventh Grade Junior High School - Akbar Sam'un; Nita Sutanti (JOSAR (Journal of Students Academic Research), 2026)
The objective of this research is to develop "Flash-Eng" flashcards as an effective instructional media to improve the vocabulary mastery of seventh-grade students at SMPN 02 Wlingi. This study addresses the common challenges faced by EFL learners, particularly the lack of engaging visual resources and students' difficulty in memorizing English vocabulary. The methodology employed in this study is Research and Development (R&D), following the systematic ADDIE model which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. In the analysis phase, it was identified that students required more interactive materials to bridge the gap between classroom theory and practical vocabulary usage. The development phase focused on creating high-quality flashcards validated by material and media experts to ensure pedagogical and technical quality. The results of the validation from experts showed that the media was categorized as "Very Good" and feasible to use. During the implementation phase, the product was tested on seventh-grade students to measure its practicality and effectiveness in a classroom setting. The findings indicate that the Flash-Eng media significantly aids students in mastering English nouns and verbs. This study concludes that integrating visual-based media into the curriculum provides a solid foundation for communicative competence.